Efeito do Distanciamento de Aerogeradores sobre a Geração Elétrica dos Parques Eólicos do Ceará. - Uchôa, Kênio Monteles (2022)
The objective of this dissertation is to analyze the effect of the distance between wind turbines on the wake effect losses and electricity generation, through simulations in Wasp software. The dissertation initially gathered data from 11 wind farms in operation in Trairi-CE and 1 in Amontada-CE: geographic coordinates, installed capacity, occupied area, wind turbine model and rotor diameter. Once the wind farm was identified, the distance between the wind turbines was measured and the ratio of the average of these distances with the respective rotor diameter was calculated. After this step, the relationship between the occupied area and installed capacity (in km²/MW) and capacity density (in MW/km²) was calculated, in order to evaluate the use of the occupied area and the concentration of the installed capacity. Then, the immobilized area (in m²year/MWh), the ratio between the occupied area over the plant's lifetime and the generation of electric energy were calculated. In order to verify the influence of the distance of wind turbines on electricity generation, a farm in operation in Amontada-CE (Icaraí) was chosen and transposed to Parnaíba (PI), where a fictitious farm was simulated in three scenarios: scenario 1 (no repositioning of wind turbines), scenario 2 (individual repositioning of wind turbines) and scenario 3 (collective repositioning of wind turbines) in Wasp. When analyzing the relationship of the average distance with the rotor diameter, TrairiCE, Icaraí and Parnaíba farms show a higher distance than the lower distance guided by the IEC 61400-12 standard; however, they are partially not in accordance with the literature and international wind farms. When compared with the ranges of the National Renewable Energy Laboratory (NREL) report, considering the relationship between occupied area and installed capacity, it was found that 5 of the 11 farms are with values above the lower range; only 1 presents capacity density with a value below the upper range, indicating for the other wind farms, low amount of occupied area and concentration of the installed capacity. As for the immobilized areas, the average of the calculated results (712.24 m²year/MWh) indicates that the analyzed immobilized areas are below the global average (1,129 m²year/MWh). The simulations of the fictitious park in Wasp presented the following results of losses by wake effect (%): 3.80% (scenario 1), 3.71% (in the best individual repositioning of scenario 2) and 3.45% (scenario 3), and net annual generated electricity (GWh): 33.596 GWh (scenario 1), 33.629 GWh (in the best individual repositioning of scenario 2) and 33.721 GWh (scenario 3)